PENGARUH MODEL PEMBELAJARAN INKUIRI SOSIAL UNTUK MENINGKATKAN KEPEKAAN SOSIAL PESERTA DIDIK (Studi Quasi Eksperimen dalam Pembelajaran IPS di Kelas V MI) - Tusriyanto, Tusriyanto (JURNAL TAPIS, 2013)
Social studies elementary school should be emphasized in social sensitivity skills in social life. Social studies has a value of practical learning, which should foster individual creative, democratic and responsible, as well as coaching and also have the burden of cultural as well as a good life, harmonious and dynamic. Social studies educators should be aware that educate participants who would implement any content social studies and social life tomorrow will be different from today. The aim of this study, is "To know the influence of social inquiry learning model to increase social sensitivity compared to students who follow the conventional learning in learning social studies in Class V Elementary School". Data collection tool used in this research is to learn the results of tests, this test is used to measure learning outcomes by increasing student social sensitivity, which is done with the pretest and posttest.The results demonstrate the ability of social sensitivity can be improved through social inquiry learning can be seen from the t to the results of the posttest with Equal Variance Not Assumed (both assumed unequal variances or using separate variance test) is 0.472 with probability 0.025. Therefore the probability <0.05 then Ho is rejected, or both the average (mean) between the experimental group and the control group was different. In other words, the experimental group had a mean score higher than the control group.Keywords:Social studies, social inquiry, social sensitivity